The Effectiveness of SIAP TARIK to Improve the Quality of Health Services - Lailul Mursyidah; Ilmi Usrotin Choiriyah; Mai Puji Lestari; Isnaini Rodiyah (Indonesian Association for Public Administration (IAPA), 2019)
SIAP TARIK (Sistem Informasi Antrian Puskesmas Tarik) is a public service innovation in health service. SIAP TARIK is the application for ordering the queue number at the Puskesmas (health center) Tarik, Sidoarjo. This research aims to know the effectiveness of SIAP TARIK to improve the quality of helath service. This quantitative descriptive research is located at Puskesmas Tarik, Sidoarjo. The respondents of this reseach were patients who visited Puskesmas Tarik using incidental sampling techniques. The data is collected through questionnaire. The data analysis techniques use descriptive analysis techniques. The result of this research show that SIAP TARIK is effective to improve the quality of health service with score 4234. The position is in the quartile interval >3300 up to 4290 which is categorized as effective. These result are indicated by the score of sistem quality, information quality, service quality, utilization, satisfaction of use, and net benefits are in effective position.